Chemical control of ufra disease of rice: a simple profitability analysis - Latif, Mohammad Abdul; Yusop, Mohd Rafii; Miah, Gous; Akter, Shamima; Ali, Md Ansar (WFL Publisher, 2013)
Multiple field trials were conducted to determine the efficacy of Furataf 5G, Arodhan 5G and Biestern 5G @ 1.0 kg a.i/ha with standard check, Furadan 5G in two ecosystems and three seasons viz. November to April irrigated ecosystem (Boro), April to July (Transplanted Aus) and July to October (Transplanted Aman) rain-fed lowland ecosystems during 1995 to 1997. All the test chemicals are effective to control the ufra disease of rice and increased yield in comparison with Furadan 5G. In respect of all seasons, Furataf 5G, Arodhan 5G, Biestern 5G increased yield recovery 2.29- 4.15, 2.59-3.40 and 3.06-3.86 t/ha in three rice genotypes respectively, which was more or loss similar to Furadan 5G (3.09-3.65 t/ha). Yield reduces due to ufra disease was 79.48% in T. Aman, while it was 93.88% and 89.11% in T. Aus and Boro rice. Application of Furataf 5G, Arodhan 5G, Biestern 5G and Furadan 5G showed 14.44-15.74, 10.09-14.31 and 12.45 -14.92 times profitable in case of T. Aus, T. Aman and Boro respectively over the control (Diseased). Simple economic analysis also revealed that ufra control with the use of three chemicals in soil treatments is profitable. Thus three chemicals may also be used as alternative to Furadan 5G.